Students’ Perceptions of PBL Usefulness - Babo Lurdes; Mendonça Jorge; Pinto Carla (Open Education Studies)
Problem-based learning (PBL) is a teaching technique in which students’ learning is conveyed using real-world problems. However, the implementation of PBL is confronted with several challenges, namely the involvement of students, the definition of the teacher’s role, and the development of effective assessment mechanisms. This paper describes and analyses a teaching framework based on PBL followed in the Differential and Integral Calculus and Statistical Models courses in a Biomedical Engineering Bachelor, at the School of Engineering, Polytechnic of Porto. In order to assess students’ points of view about the effectiveness of this PBL approach with regard to knowledge acquisition, development of soft skills, and assessment methods, a questionnaire was administered at the terminus of the semester. Data analysis revealed that newcomers are more likely to use PBL, while second-year students feel more pressure and report more workload with this type of assessment. In this regard, we consider that factors such as maturity, education level, workload in other courses, and prior PBL experience may influence students’ willingness to adhere to PBL.